PENENTUAN TINGKAT EROSI MENGGUNAKAN METODE USLE DAN SISTEM INFORMASI GEOGRAFIS (SIG) PADA SUB DAS KEDUNG BULUS, KABUPATEN KEBUMEN, JAWA TENGAH - , LIDYA KARTINI GULTOM; , Prof. Dr. Ir. Putu Sudira, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High rainfall intensity causes erosion because energy of rainfall breaks soil aggregates and flows into the lower places. The erosion may also occur due to land management which is not accordance with its capacity, without considering the environment condition. The study was conducted in Kedung Bulus Watershed, in Kebumen Regency, Central Java Province. The amount of erosion was predicted using USLE (Universal Soil Loss Equation) and GIS (Geographical Information System). Based on the method, several maps were used including soil type, land use, slope, and rainfall erosivity maps. Those four maps were overlaid to obtain erosion classes and its area affected. The prediction of erosion was compared with sedimen taken from the outlet of the sub Watershed. The result of the research in Kedung Bulus sub Watershed, indicated that there were 803 land units. After classifying, the area was dominated by very light class erosion (99,45%) and the rest was classified as a light class erosion. The result of the validity test indicated that there was not significantly different between the observed and predicted erosion using USLE. It was denoted by lower value of tcalculate compared to ttable